2020
DOI: 10.1111/jvim.15812
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐beta plasma and cerebrospinal fluid biomarkers in aged dogs with cognitive dysfunction syndrome

Abstract: Background Cognitive dysfunction syndrome (CDS) is a common progressive neurodegenerative disease that is poorly defined. Specific multitargeted protocols do not exist for setting the diagnosis and the prognosis of the syndrome. Hypothesis/Objectives To quantify Aβ42 and Aβ40 peptides in blood and cerebrospinal fluid (CSF) and to investigate their contribution to CCDS. Animals A total of 61 dogs from a hospital population. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The mean plasma Aβ 42 level with refractory idiopathic epilepsy was significantly greater levels when compared to normal dogs (99 pg/ mL vs. 5.9 pg/mL, p < 0.05, Figure 1). Similarly, it was observed that dogs with cognitive impairment exhibited increased levels of plasma Aβ 42 (31,32,34).…”
Section: Plasma Levels Of Aβ 42 In Dogs With Epilepsy and Healthy Dogsmentioning
confidence: 92%
“…The mean plasma Aβ 42 level with refractory idiopathic epilepsy was significantly greater levels when compared to normal dogs (99 pg/ mL vs. 5.9 pg/mL, p < 0.05, Figure 1). Similarly, it was observed that dogs with cognitive impairment exhibited increased levels of plasma Aβ 42 (31,32,34).…”
Section: Plasma Levels Of Aβ 42 In Dogs With Epilepsy and Healthy Dogsmentioning
confidence: 92%
“…Routine blood tests in elderly dogs would show a mild increase of liver enzymes [ 31 ], with no other salient abnormalities being definitely confirmed to date. In canine patients with CDS, detection and quantification of soluble oligomers of β-amyloid fragments 1–40 and 1–42, hyperphosphorylated tau protein, and neurofilament light chain are considered promising, although not yet validated, blood biomarkers [ 31 , 32 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…The prevalence of CCDS is up to 60% in dogs, predominantly >11 years; however, the actual diagnosis rate remains quite low, at approximately 2% (5,12,14). Species-specific differences in CCDS have not been identified (12).…”
Section: Introductionmentioning
confidence: 99%
“…With the extended lifespan of companion animals, the importance of CCDS, a representative geriatric disease, is increasing. However, accurate treatments remained elusive until recently (14). Various therapeutic approaches have been reported to enhance cognitive abilities and improve quality of life (3).…”
Section: Introductionmentioning
confidence: 99%